Evaluation of task sharing as a workforce optimization strategy in pediatric oncology - Hashmi, Saman K.; Raza, Muhammad Rafie; Ashraf, Muhammad Shamvil; Qadir, Ghulam; Imam, Uzma; Fadoo, Zehra; Ahmad, Alia; Saeed, Haleema; Ghafoor, Tariq; Yasmeen, Nuzhat; Rana, Zulfiqar A.; Hamid, Muhammad Haroon; et al. (Frontiers in Oncology, 2025)
Task sharing is a pragmatic response to the growing shortage of pediatric oncologists globally, especially in low- and middle-income countries (LMICs). However, there have been limited evaluations of how task sharing has been implemented. In this study, we sought to determine the roles and responsibilities of task-sharing physicians (TSPs) in one LMIC, Pakistan. A multicenter cross-sectional study was conducted across 16 hospitals with secondary- to quaternary-level pediatric oncology facilities. An online survey was used to determine task-sharing models, the responsibilities of TSPs, and the level of supervision. Pediatric oncologists were present at 13 of the 16 centers, with a median of 2 pediatric oncologists per center. We found that TSPs included tiers of medical officers/general physicians and pediatricians. They provided inpatient, outpatient, overnight and emergency room coverage. TSPs could participate in defining cancer diagnosis and risk-stratification (n = 9; 56%), selecting initial chemotherapy plans for patients with newly diagnosed cancer (n = 6; 38%) and modifying chemotherapy on the basis of toxicities (n = 6; 38%) under supervision of a pediatric oncologist. In addition, TSPs could write intravenous chemotherapy orders (n = 10; 63%) and prescribe oral chemotherapy (n = 10; 63%). Furthermore, they could independently perform procedures, such as lumbar punctures (n = 15; 94%), intrathecal chemotherapy administration (n = 11; 69%), and bone marrow aspirates and biopsies (n = 11; 69%). TSPs are critical in the pediatric oncology workforce with responsibilities across the pediatric cancer care continuum.